Predictable Pleasures : Food and the Pursuit of Balance in Rural Yucatán - Wynne, Lauren A. (Book collections on Project MUSE., 2020)
"Wynne examines the centrality of food in rural Yucatán and how residents practice care, as exercised through food, to negotiate anxieties, achieve desired bodily and social status, and maintain valued cultural forms"--